C3S:research of CI-based concurrent transmission strategy for intelligent sensing system - Yanyan MAO; Dapeng CHENG; Yanli FENG; Quansheng DOU; Dashe LI (Tongxin xuebao)
Concurrent transmission technology has important sense for Intelligent Sensing System (ISS).The C3S strategy based with constructive interference (CI) was proposed.C3S was composed of intelligent clock synchronization layer,intelligent energy consumption allocation layer and intelligent parallel pipeline layer.The intelligent clock synchronization layer designed ICCA,a CI-based intelligent clock calibration algorithm.The intelligent energy allocation layer designed CIES,a energy adaptive scheduling scheme for CI,Moreover,a CI-based parallel pipeline CI2P was implemented in the intelligent parallel pipeline layer.The experimental results show that the C3S strategy can effectively improve the packet receiving rate of the concurrent transmission in ISS.It can also reduce the energy consumption of ISS and improve the channel utilization rate of ISS.